Non-alcoholic Fatty Liver Disease Related to Metabolic Syndrome: a Case-control Study - Neneng Ratnasari; Hemi Senorita; Riska Humardewayani Adie; Putut Bayupurnama; Sutanto Maduseno; Siti Nurdjanah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
Background: Non-alcoholic fatty liver disease (NAFLD) is a benign condition, but it can go for years and progress to liver cirrhosis or eventually to liver cancer. Metabolic syndrome (MS) is a condition associated with NAFLD. This study was aimed to know the risk factors of NAFLD related to metabolic syndrome. Method: A case-control study was performed in NAFLD patients with or without MS and healthy individuals. All subjects were recruited from population that underwent routine medical check-up at Sardjito Hospital, Jogjakarta, during March 2007–August 2008. Diagnosis of NAFLD is defined based on clinical and liver ultrasound findings. Diagnosis of MS is defined by International Diabetes Federation on criteria for the diagnosis of MS. Data were analyzed by using T-test, ANOVA and linear regression. Odds ratio (OR) (95% CI and p 0.05) was calculated by cross-tab analysis. Results: There were 84 patients enrolled in the study (group I = 30 NAFLD + MS subjects; group II = 26 NAFLD patients; group III = 28 healthy). The data showed statistically significant Results in waist circumference, systole blood pressure, fasting glucose, triglyceride, high density lipoprotein (HDL) cholesterol level, homeostasis models assessment index ratio (HOMA-IR), free fatty acid (FFA), and adiponectin. The ANOVA and linear regression test among NAFLD groups showed significant difference only on HDL-cholesterol and FFA level. The lowest OR was 1.674 for HDL-cholesterol and highest OR was 13.571 for triglyceride. Conclusion: The independent factors of NAFLD related to metabolic syndrome are FFA and HDL- cholesterol level, even though a decreasing of HDL-cholesterol level has a lowest risk of NAFLD. Keywords: NAFLD, metabolic syndrome, FFA, adiponectin, HDL-cholesterol